Por uma eugenia latino-americana: Victor Delfino e Renato Kehl - Joao Italo de Oliveira e Silva (2008)
This current work shows the formation process of the Brazilian and Argentine eugenic movement under a bigger project of scientific cooperation among Latin-Americans scholars. It highlights the bonds built between Renato Kehl, a renowned Brazilian doctor, and Victor Delfino - editor of La Semana Médica, a main medical argentine journal. This dissertation reveals an intense intellectual exchange embodied by many latin-americans thinkers who designed a handful of measures and proposals that could promote the improvement of their countries populations. This paper intends to compare these eugenic movements Argentine and Brazilian , which were quite similar during the beginning of the twentieth century, but drifted apart under the dictatorialship regimes over the 1930s.